2021
DOI: 10.3390/microorganisms9061114
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics Associated with the Development of Cystoid Macular Edema in Patients with Cytomegalovirus Retinitis

Abstract: We evaluated the incidence and characteristics of eyes with cytomegalovirus (CMV) retinitis according to the occurrence of cystoid macular edema (CME) and identified the risk factors of its occurrence. Patients diagnosed with CMV retinitis and examined using optical coherence tomography were classified according to the development of CME. The CME group was further divided according to the presence of active retinitis at the time of CME development. The demographics, serologic findings, ophthalmic presentations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Cystoid macular oedema is one of the clinical manifestations of CMV retinitis [ 8 ]. CMV retinitis patients with cystoid macular oedema have poorer vision, longer virus duration, and poor prognosis [ 18 ]. Cystoid macular oedema usually develops before the injection of ganciclovir.…”
Section: Discussionmentioning
confidence: 99%
“…Cystoid macular oedema is one of the clinical manifestations of CMV retinitis [ 8 ]. CMV retinitis patients with cystoid macular oedema have poorer vision, longer virus duration, and poor prognosis [ 18 ]. Cystoid macular oedema usually develops before the injection of ganciclovir.…”
Section: Discussionmentioning
confidence: 99%
“…After primary infection, CMV remains in the host cells in latent form. The risk of CMV recurrence is dependent on the level of incompetency of the immune system [35][36][37][38][39] , manifested as an impairment of T-cell immunity, including the presence and function of CMV-specific cytotoxic T lymphocytes. From the regression analysis, we found that the extent of fundus lesions, and the presence of vitreous haze were related to retinitis recurrence, among which the extent of fundus lesions has a significant association with the recurrence of CMVR.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers employ the term "oncomodulation" to explain HCMV's role in malignancies, even though human CMV is not an oncogenic virus. The fact that HCMV is frequently found in tumor tissues could be explained by the fact that it promotes tumor growth while not being an oncogenic virus (Kwon et al, 2021). Oncomodulation occurs when HCMV infects tumor cells and alters their aggressiveness (Touma et al, 2021).…”
Section: The High Presence Of Hcmv Pp71 Proteins Correlate With P63 E...mentioning
confidence: 99%